Body language to increase the speaking skill of students of ninth grade at escuela de educación básica Teodoro Wolf. Santa Elena, province of Santa Elena, school year 2016-2017. - Proaño Proaño, Miriam Elizabeth (2016)
This paper investigated how young English language learners reacted to the implementation of movements and gestures in order to enhance their speaking skills in the classroom. The TPR Methodology is the primary resource which contributed to provide innovative strategies in the English as a Foreign Language (EFL) classroom, this should be implemented so that students could feel motivated to develop their English communicative skills. In this study, common movements motivated students to be continuously engaged. For this reason the English teacher has a relevant role of guide and she should keep the interaction between students in the learning process, creating a good rapport. The participants of this qualitative study, young English language learners, were observed in a constructivist atmosphere, while data was gathered from observations, interviews and surveys. Speaking is an essential skill which could be developed through using Body Language which promote the enhancement of this skill. Using mimics and movements is one appropriate way to integrate Body Language in EFL classrooms and it provides opportunities to improve the speaking skills using it as a supplementary and highly beneficial resource. The present research shows the improvement of the speaking skill of the ninth grade students from Escuela de Educaciòn Bàsica Teodoro Wolf, with the help of a Body Language Manual, created especially for this study, in which through a series of dynamic activities they engaged in speaking activities.